Social learning in the collaborative management of community forests: lessons from the field - Buck, L.; Wollenberg, Eva Karoline; Edmunds, D. (Center for International Forestry Research, 2001)
Community forest management worldwide has involved diverse types and varying levels of success in social learning, yet little efforts has been made to analyze these experiences and link them to emerging social learning theory. This chapter is a synthesis of the contributions of the workshop participants to indicate what social learning is and how it could be enhanced. The most notable contribution of chapters was in making learning phenomena more visible and giving people the concepts and labels with which to analyze their experiences. Important institutional arrangements underlying social learning were facilitation and the platforms around which stakeholders met and learned. Different types of learning, the avenues for learning and the factors influencing learning are reviewed. Any endeavor to learn jointly must be assessed and implemented with sensitivity and strategic thingking to who can or should be participating and how.